Venomics of Tropidolaemus wagleri, the sexually dimorphic temple pit viper: Unveiling a deeply conserved atypical toxin arsenal - Tan, C.H.; Tan, K.Y.; Yap, M.K.K.; Tan, N.H. (Nature Publishing Group, 2017)
Tropidolaemus wagleri (temple pit viper) is a medically important snake in Southeast Asia. It displays distinct sexual dimorphism and prey specificity, however its venomics and inter-sex venom variation have not been thoroughly investigated. Applying reverse-phase HPLC, we demonstrated that the venom profiles were not significantly affected by sex and geographical locality (Peninsular Malaya, insular Penang, insular Sumatra) of the snakes. Essentially, venoms of both sexes share comparable intravenous median lethal dose (LD50) (0.56-0.63 μg/g) and cause neurotoxic envenomation in mice. LCMS/MS identified six waglerin forms as the predominant lethal principles, comprising 38.2% of total venom proteins. Fourteen other toxin-protein families identified include phospholipase A2, serine proteinase, snaclec and metalloproteinase. In mice, HPLC fractions containing these proteins showed insignificant contribution to the overall venom lethality. Besides, the unique elution pattern of approximately 34.5% of non-lethal, low molecular mass proteins (3-5 kDa) on HPLC could be potential biomarker for this primitive crotalid species. Together, the study unveiled the venom proteome of T. wagleri that is atypical among many pit vipers as it comprises abundant neurotoxic peptides (waglerins) but little hemotoxic proteinases. The findings also revealed that the venom is relatively well conserved intraspecifically despite the drastic morphological differences between sexes.